Research trends in the application of artificial intelligence in physical therapy rehabilitation: a bibliometric study: Research trends in artificial intelligence in physical therapy rehabilitation. - Subbarayalu, Arun Vijay; Mohamed Idhris; Prabaharan, Sivasankar; Kamalasanan, Ajayan; Anandraj Samuel, Spurgeon; Sakthivel, Muhil; Pattukuthu, Abdurahiman; Pandiyarajan, Anand; Barkath Ali, Mohammed; Purushothaman, Vinosh Kumar; Rubavathi Marimuthu, Palanivel (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Artificial intelligence (AI) assists physical therapy (PT) rehabilitation by assessing health improvement and tracking patients' progress toward individualized rehabilitation goals that are in line with their capabilities and needs. The aim of this study was to uncover research trends in the application of AI in PT rehabilitation through a bibliometric approach. Methods: An electronic search of the Web of Science (WoS) database was conducted on October 4, 2023 using specific keywords. The data was downloaded using the WoS database in a WoS plain text file and analyzed using various software, namely R Studio (biblioshiny), Visualization of Similarities Viewer and NetDraw. Results:  Between 2014 and 2023, 1216 research documents on AI in PT rehabilitation were published by various authors worldwide. Most documents (15.21%; n=185) were published in 2022. The journal “Sensors” published 3.21% (n=39) of the research documents and showed 298 citations. Another journal, “Journal of Neuroengineering and Rehabilitation”, published 2.22% (n=27) and showed 1406 citations. The document published by the author “Maciejasz P (2014)” in the “Journal of NeuroEngineering and Rehabilitation” had a high total citation score of 706. The United States has contributed significantly to AI-related documents in PT rehabilitation. Conclusions: The publication of AI in PT rehabilitation-related documents has shown an upward trend since 2015. These documents were actively published by various journals and authors around the world. Global researchers can further improve their affinity for AI in PT rehabilitation by providing more high-quality research papers in the future.